PRACTICE AND CHALLENGES ON AUTHENTIC ASSESSMENT OF EFL YOUNG LEARNER’S WRITING SKILLS - Azizah, Rizki; Muaamaroh; Mauly Halwat Hikmah (Holistik Analisis Nexus, 2024)
Young learners’ English writing skill in EFL classroom setting is as essential to take into consideration as other English skills. For ensuring the progression-making, in term of monitoring the level of achievement, the authentic assessment offers various advantages that should not be taken for granted. This study aimed at investigating, 1) the assessment practice in the classroom, 2) the effectiveness of authentic assessment practice for assessing writing skill, and 3) the challenges of the practice. This study was a descriptive case study. The population of the study encompassed 31 learners in grade-5 elementary school. The instruments used for collecting the data were field notes yielded from classroom observation, transcript interview, and related documents. The result of the study performed that (1) the teacher employs several types of assessment, yet authentic assessment is the most preferrable in the practice, (2) the authentic assessment practice in the classroom is effectively depicting learners’ actual competence, comprising real-world relevance, and encouraging evaluation, and (3) the teacher encounters the challenging experience in designing acceptable assessment for learners with diverse level of English competence and the sufficient time, as well. In summary, this study has torched a light on the practice of authentic assessment in originally realizing the function of assessment. The different school setting, teaching experiences, learners’ language proficiency skills, and classroom environment might bring about a distinct result.